2017
DOI: 10.1016/j.neuroscience.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential behavioral sensitivity to carbon dioxide (CO2) inhalation in rats

Abstract: Inhalation of carbon dioxide (CO2) is frequently employed as a biological challenge to evoke intense fear and anxiety. In individuals with panic disorder, CO2 reliably evokes panic attacks. Sensitivity to CO2 is highly heterogeneous among individuals, and although a genetic component is implicated, underlying mechanisms are not clear. Preclinical models that can simulate differential responsivity to CO2 are therefore relevant. In the current study we investigated CO2-evoked behavioral responses in four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Some evidence suggest that the posture and proprioceptive inputs from the abdominal wall may also affect active expiration 61 , 62 . Considering that the LC presents specialized subgroups of noradrenergic neurons, projecting to prefrontal cortex, that are involved in the anxiogenic behaviours 32 , 33 and that inhalation of CO 2 -enriched air can produce anxiety and fear-like behaviours 63 , we cannot rule out that changes in the behavioural responses to hypercapnia, after acute A6 inhibition, may contribute to the reductions in both active expiration magnitude and incidence through postural changes and even by Abd proprioceptive components.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggest that the posture and proprioceptive inputs from the abdominal wall may also affect active expiration 61 , 62 . Considering that the LC presents specialized subgroups of noradrenergic neurons, projecting to prefrontal cortex, that are involved in the anxiogenic behaviours 32 , 33 and that inhalation of CO 2 -enriched air can produce anxiety and fear-like behaviours 63 , we cannot rule out that changes in the behavioural responses to hypercapnia, after acute A6 inhibition, may contribute to the reductions in both active expiration magnitude and incidence through postural changes and even by Abd proprioceptive components.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of 5% concentration was based on respiratory physiology experiments, where the CO2 concentration usually used is 8% 52 . It has been shown that a concentration of 10% can increase immobility bouts in Long-Evans Rats, suggesting a certain level of anxiety 53 . We therefore searched for the lowest concentration able to induce a change in the amplitude and/or respiratory frequency.…”
Section: Lfp and Respiration Recordingmentioning
confidence: 99%
“…The representational nature of animal models demands that its adequacy as an hypothesis-generating device is satisfactory (Belzung & Lemoine, 2011;Maximino & van der Staay, 2019;van der Staay, 2006;Willner, 1986Willner, , 1991. This is the issue of validity.…”
Section: Model Validity and Theories Of Panic Disordermentioning
confidence: 99%
“…These animals also show attenuated c-Fos-like responses in the lateral wings of the dorsal raphe nucleus (lwDRN) and the VLPAG . Similarly, different rat strains show different sensitivities to CO 2 inhalation (Winter, Ahlbrand, Naik, & Sah, 2017), and behavioral extremes are an interesting source of variation to investigate vulnerabilities in disordered animals (van der Staay, 2006). Interestingly, CO 2 -sensitive strains show more serotonergic neurons in the lwDRN and the VLPAG and more adrenergic neurons in the locus coeruleus (Winter et al, 2017).…”
Section: Hypercapnia-induced Behavioral and Physiological Responsesmentioning
confidence: 99%